IMPLEMENTASI GAMIFIKASI BERBASIS WAYGROUND DALAM MOTIVASI BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SEKOLAH DASAR NEGERI PUHGOGOR 01 - Aura sekar; I Made Ratih Rosanawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of Wayground-based gamification in the motivation of learning Pancasila Education of fifth-grade students at Puhgogor 01 Public Elementary School. The study used a descriptive method with a qualitative approach. The research subjects consisted of teachers and fifth-grade students of Puhgogor 01 Public Elementary School. Data collection techniques were carried out through interviews, observation, and documentation. Data validity was tested using source triangulation and method triangulation. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the implementation of Wayground-based gamification was carried out systematically through the stages of planning, implementation, and evaluation of learning. During the implementation stage, students were actively involved in interactive discussion groups through game features, scores, and leaderboards. The use of Wayground was able to increase student learning motivation as shown by increased enthusiasm, interest, active involvement, and the desire to achieve the best results. Supporting factors for implementation include thorough learning planning, Wayground interactive features, teacher ability to manage learning, and a conducive classroom atmosphere. Inhibiting factors include technical constraints, limited facilities and infrastructure, and limited Wayground features. The conclusion of this study indicates that Wayground-based gamification can be an effective alternative learning medium to support increased motivation to learn Pancasila Education in elementary school students.